Factors associated with late presentation for HIV care in adolescents in Spain. Issue 11 (30th September 2022) - Epalza, Cristina; Domínguez‐Rodríguez, Sara; Cervantes, Eloisa; Jiménez de Ory, Santiago; Frick, Marie Antoinette; Fortuny, Clàudia; Soler‐Palacín, Pere; Prieto‐Tato, Luis; Sainz, Talía; Carreras‐Abad, Clara; Montero Alonso, Marta; de Zárraga Fernández, Miguel Alberto; et al.
Abstract: Objective: Late presenters (LP) for HIV care are associated with higher morbidity and mortality rates. Our aim was to describe the characteristics associated with LP among adolescents in Spain. Identification of particular features may help in the design of strategies for improvement. Methods: Late‐presenting adolescents diagnosed at 12–19 years of age and enrolled in the Spanish paediatric and adult HIV/AIDS cohorts (CoRIS‐CoRISpe) from 2004 to 2019 were selected. LP were defined as those presenting with CD4 count <350 cells/mm 3 or an AIDS‐defining event in the 6 months following HIV diagnosis. Confirmed low CD4 count in the next 3 months and before antiretroviral treatment initiation defined confirmed LP (cLP). Results: Of 410 adolescents newly diagnosed with HIV, 303 (73.9%) had available data for assessing late presentation. Of these, 34.7% were LP and 23.7% were cLP. The median CD4 count for cLP was 235 cells/mm 3 (interquartile range 122–285). In a multivariable analysis, adolescents at the highest risk of late presentation were early adolescents (age 12–14 years; odds ratio [OR] 6.50; 95% confidence interval [CI] 2.61–18.2), middle adolescents (age 15–17 years; OR 1.85; 95% CI 0.92–3.59), and adolescents born abroad (OR 1.71; 95% CI 0.97–3.00), particularly those of African origin (OR 3.08; 95% CI 1.38–6.79). Conclusions: One‐quarter of adolescents presented late for HIV care in Spain. Early adolescents, middle adolescents, and those born abroad presented a sevenfold, twofold, and twofold higher risk of being cLP, respectively. Enhancing the awareness of HIV risk and the access to care, especially for younger and foreign adolescents, could help reduce late presentation and tackle the adolescent HIV epidemic.